On Cuteness: Unlocking the Parental Brain and Beyond - Kringelbach, Morten L.; Stark, Eloise A.; Alexander, Catherine; Bornstein, Marc H.; Stein, Alan (Trends in cognitive sciences, 2016)
Cuteness in offspring is a potent protective mechanism that ensures survival for otherwise completely dependent infants. Previous research has linked cuteness to early ethological ideas of a ‘Kindchenschema’ (infant schema) where infant facial features serve as ‘innate releasing mechanisms’ for instinctual caregiving behaviours. We propose extending the concept of cuteness beyond visual features to include positive infant sounds and smells. Evidence from behavioural and neuroimaging studies links this extended concept of cuteness to simple ‘instinctual’ behaviours and to caregiving, protection, and complex emotions. We review how cuteness supports key parental capacities by igniting fast privileged neural activity followed by slower processing in large brain networks also involved in play, empathy, and perhaps even higher-order moral emotions. The parent–infant relation is fundamental to infant survival and development. Cuteness has emerged as an important factor for attracting caregiver attention and affection. Cuteness is not limited to visual infant features, but is also found in positive sounds and smells. Neuroimaging has started to identify how survival-related infant-positive and negative stimuli elicit core affective brain activity through fast attentional biasing and slow appraisal processes. Beyond caregiving, cuteness has a key role in facilitating social relations, pleasure, and well-being, as well as increasing empathy and compassion.